STUDI DESKRIPTIF LITERASI SAINS SISWA MELALUI METODE FIELD TRIP DALAM PEMBELAJARAN IPAS KELAS IV SD NEGERI SAWOJAJAR 01 - Qotrunada, Nida; Saefudin Wahid, Farhan; Toharudin, Moh. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low level of scientific literacy among elementary school students and the importance of meaningful learning. The purpose of this study is to describe the scientific literacy skills of fourth-grade students in IPAS learning through the field trip method and to identify the factors that influence them. This study uses a descriptive qualitative approach with the subjects consisting of a fourth-grade teacher and students at SD Negeri Sawojajar 01. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing with triangulation for validity. The results show that students’ scientific literacy begins to develop through field trip activities, as indicated by their ability to observe, explain phenomena, and relate them to daily life, although differences in students’ abilities still exist due to variations in participation and learning conditions. Keywords: scientific literacy, field trip, IPAS, elementary school.